Family Engagement in Nurturing Students’ Resilience During Remote Learning in COVID-19 Pandemic - Sururin Sururin; M. C. Mahmuda; Moh. Muslim (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2020)
AbstractThis research aims (1) to explore the family's role in remote learning practice and (2) to find out what family can do to nurture students' resilience during the COVID-19 pandemic. This study employed qualitative descriptive methodology with a case study approach to obtain and analyse data narratively. The findings of this study are: (1) Family become the observer of students’ resilience and personality development, their observation will determine teachers’ approach in teaching and educating resilience virtue. Their role as facilitator in home learning shows their support and passion to engage with their children’s learning process. (2) Direct assistance during video conferencing is part of collaboration between school and family to participate in resilience-building, but only few parents did so due to diversed backgrounds. AbstrakPenelitian ini bertujuan (1) untuk mengeksplorasi peran keluarga dalam praktik pembelajaran jarak jauh dan (2) untuk mengetahui apa yang dapat dilakukan keluarga untuk memelihara ketahanan siswa selama pandemi COVID-19. Penelitian ini menggunakan metodologi deskriptif kualitatif dengan pendekatan studi kasus untuk memperoleh dan menganalisis data secara naratif. Temuan penelitian ini adalah: (1) Keluarga menjadi pengamat ketahanan dan perkembangan kepribadian siswa, observasi mereka akan menentukan pendekatan guru dalam mengajar dan mendidik ketahanan kebajikan. Peran mereka sebagai fasilitator dalam pembelajaran di rumah menunjukkan dukungan dan semangat mereka untuk terlibat dengan proses pembelajaran anak-anak mereka. (2) Bantuan langsung selama konferensi video merupakan bagian dari kerjasama antara sekolah dan keluarga untuk berpartisipasi dalam pembangunan ketahanan, tetapi hanya sedikit orang tua yang melakukannya karena latar belakang yang berbeda.. How to Cite: Sururin, Mahmuda, M.C., Muslim, M. (2020). Family Engagement in Nurturing Students’ Resilience During Remote Learning in COVID-19 Pandemic. TARBIYA: Journal of Education in Muslim Society, 7(2), 204-216. doi:10.15408/tjems.v7i2.20582.